Operational Performance of Palabuhanratu Nusantara Fishing Port (NFP) Sukabumi, West Java - Agus Suherman; Faik Kurohman; Bogi Budi Jayanto (JURNAL PERIKANAN DAN KELAUTAN, 2020)
This study aims to analyze operational activities and determinants of the performance of NFP Palabuhanratu. This research was conducted in January 2020 to April 2020 at NFP Palabuhanratu. Data analysis was performed using two methods; the first is a descriptive method which is to analyze the operational activities of NFP Palabuhanratu; the second is the Structural Equation Model (SEM) method, which is to determine the determinants of the performance of NFP Palabuhanratu. The results of this study indicate that the operational activities of NFP Palabuhanratu continue to increase. Fishing boat visits in 2019 increased was 37.136 . Fish production in 2019 increase as many as 36.44% compared to the previous year. Based on SEM test results, Internal has the most influence on NFP performance. This shows that the higher the internal, the higher the performance of NFP. Therefore the management of NFP Pelabuhan Ratu is expected to improve the quality of HR / NFP Managers in the form of education, skills and work culture, increase the budget allocation of UPT, improve the quality of Fishermen / Processors / Marketers in the form of education, skills and experience, increase fisherman productivity in the form of technology, income and production. If this is done well by the NFP management, then Internal can be increased. Thus the performance of Palabuhanratu NFP increased